Novel Predictor for Recurrent Atrial Fibrillation After Radiofrequency Catheter Ablation (RFCA): A Review of Literature to Explore The Role of Carbohydrate Antigen-125 (PCA-125) in Plasma - Fahmi Ikram, Muhammad; Josua Barutu, Andri; Rhizkikah Chairiya, Putri; Izza Mora Lubis, Azhzhilla; Multazam Rangkuti, Ahmad Aziz; Rahman, Dieny Oktavia; Faiz Ikram, Muhammad (Jurnal KESANS : Kesehatan dan Sains, 2025)
Atrial Fibrillation (AF), the most prevalent variety of arrhythmia has an overwhelming prevalence in people over 65 years old, rendering it among the leading cardiovascular concerns. A literature search up to 2012 was carried out, including the following data bases: Medline, Google Scholar and Web of Science. The boolean terms word of this search were “Plasma Carbohydrate Antigen-125 OR PCA-125” AND “Radiofrequency Catheter Ablation OR RFCA” AND “Atrial Fibrillation OR AF” AND “Recurrent”. 36 articles are included in this review. Carbohydrate Antigen-125 (CA-125) expression shows its potency to predict a recurrent AF after RFCA procedures. CA-125 is released from mesothelial cells through protein cleavage, then released into body fluids, which play a role in protecting epithelial surfaces through lubrication and hydration processes. Myocardial remodeling results in pathological cardiomyocyte hypertrophy with re-expression of embryonic genes. During this process, proto-oncogenes are activated, which stimulate growth factors present in the embryonic heart, leading to increased CA-125 levels. Elevated levels of CA-125 in plasma may be an interesting option as an independent predictor of recurrent AF after RFCA.